Network Analyses Reveal Shifts in Transcript Profiles and Metabolites That Accompany the Expression of SUN and an Elongated Tomato Fruit. Issue 3 (4th May 2015) - Clevenger, Josh P.; Van Houten, Jason; Blackwood, Michelle; Rodríguez, Gustavo Rubén; Jikumaru, Yusuke; Kamiya, Yuji; Kusano, Miyako; Saito, Kazuki; Visa, Sofia; van der Knaap, Esther
Abstract : High expression of a gene that controls tomato shape is accompanied by dramatic shifts in gene expression and metabolite and hormone accumulation during the early stages of fruit development. Abstract: SUN controls elongated tomato ( Solanum lycopersicum ) shape early in fruit development through changes in cell number along the different axes of growth. The gene encodes a member of the IQ domain family characterized by a calmodulin binding motif. To gain insights into the role of SUN in regulating organ shape, we characterized genome-wide transcriptional changes and metabolite and hormone accumulation after pollination and fertilization in wild-type and SUN fruit tissues. Pericarp, seed/placenta, and columella tissues were collected at 4, 7, and 10 d post anthesis. Pairwise comparisons between SUN and the wild type identified 3, 154 significant differentially expressed genes that cluster in distinct gene regulatory networks. Gene regulatory networks that were enriched for cell division, calcium/transport, lipid/hormone, cell wall, secondary metabolism, and patterning processes contributed to profound shifts in gene expression in the different fruit tissues as a consequence of high expression of SUN . Promoter motif searches identified putative cis-elements recognized by known transcription factors and motifs related to mitotic-specific activator sequences. Hormone levels did not change dramatically, but some metabolite levels were significantly altered, namely participants in glycolysis and the tricarboxylic acid cycle. Also, hormone and primary metabolite networks shifted in SUN compared with wild-type fruit. Our findings imply that SUN indirectly leads to changes in gene expression, most strongly those involved in cell division, cell wall, and patterning-related processes. When evaluating global coregulation in SUN fruit, the main node represented genes involved in calcium-regulated processes, suggesting that SUN and its calmodulin binding domain impact fruit shape through calcium signaling.